Whole exome sequencing uncovered highly penetrant recessive mutations for a spectrum of rare genetic pediatric diseases in Bangladesh - Hosneara Akter (Nature Portfolio, 2021)
Abstract Collectively, rare genetic diseases affect a significant number of individuals worldwide. In this study, we have conducted whole-exome sequencing (WES) and identified underlying pathogenic or likely pathogenic variants in five children with rare genetic diseases. We present evidence for disease-causing autosomal recessive variants in a range of disease-associated genes such as DHH-associated 46,XY gonadal dysgenesis (GD) or 46,XY sex reversal 7, GNPTAB-associated mucolipidosis II alpha/beta (ML II), BBS1-associated Bardet–Biedl Syndrome (BBS), SURF1-associated Leigh Syndrome (LS) and AP4B1-associated spastic paraplegia-47 (SPG47) in unrelated affected members from Bangladesh. Our analysis pipeline detected three homozygous mutations, including a novel c. 863 G > C (p.Pro288Arg) variant in DHH, and two compound heterozygous variants, including two novel variants: c.2972dupT (p.Met991Ilefs*) in GNPTAB and c.229 G > C (p.Gly77Arg) in SURF1. All mutations were validated by Sanger sequencing. Collectively, this study adds to the genetic heterogeneity of rare genetic diseases and is the first report elucidating the genetic profile of (consanguineous and nonconsanguineous) rare genetic diseases in the Bangladesh population.